Recent Publications (Quarterly Journal of Economics, 1961)
Recent Publications Get access The Quarterly Journal of Economics, Volume 75, Issue 3, August 1961, Pages 508–514, https://doi.org/10.1093/qje/75.3.508 Published: 01 August 1961